التعليل بلزوم الطريق عند أيب حامت الرازي: تعريفه وقرائنه - Muhamad Rozaimi bin Ramle; Ahmad Kamil bin Jamilin; Sultan Sanad al-Akaileh (Universiti Sains Islam Malaysia, 2024)
JOHS Vol 3. No 1. June 2018